DOI: 10.18130/v3bh0k
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse and self-regulation : risk factors for heroin addiction

Abstract: Abused children often develop externalizing problems and substance abuse disorders later in life. The present study describes correlates of childhood abuse and heroin addiction with particular attention to the role of behavioral self-regulation and types of maltreatment. Self-regulation is operationalized as having factors of impulsivity. aggression, and inattention. 130 opiate addicts and matched controls completed the Childhood Trauma Questionnaire, the Eysenck Personality Questionnaire, the Buss Durkee Host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
(171 reference statements)
0
5
0
Order By: Relevance
“…Tangney et al (2004) concluded that students with heightened levels of self-control gain innumerable benefits over their more impulsive peers; one of which is considerably decreasing the likelihood of developing a substance abuse problem. Identical findings were discovered in more topicspecific analyses using self-control and its effect on substance abuse (Wills et al 1995), and heroin addiction (Storey 1999), respectively. Without the social restraint and internal discipline that comes with delaying gratification, a continual downward spiral can ultimately ensue, leading to a number of negative and socially-unacceptable behaviours.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Tangney et al (2004) concluded that students with heightened levels of self-control gain innumerable benefits over their more impulsive peers; one of which is considerably decreasing the likelihood of developing a substance abuse problem. Identical findings were discovered in more topicspecific analyses using self-control and its effect on substance abuse (Wills et al 1995), and heroin addiction (Storey 1999), respectively. Without the social restraint and internal discipline that comes with delaying gratification, a continual downward spiral can ultimately ensue, leading to a number of negative and socially-unacceptable behaviours.…”
Section: Introductionmentioning
confidence: 61%
“…Youths' inability to motivate themselves to control their impulses in relation to gratification control has been associated with behaviour that is progressively destructive and deadly such as substance abuse (Kirby et al 1999;Richards et al 1999;Storey 1999;Wills et al 1995) and violence (Cherek et al 1997;Dolan and Fullam 2004;Tangney et al 1991). Such findings have given rise to the realization that a student's inability to sufficiently delay gratification can be a gateway to a multitude of societal ills that permeate into institutions of learning (Wulfert et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have linked impulse control problems to deficits in self-control. Storey (1999) concluded that poor self-regulation, as assessed by the Barratt Impulsivity Scale, was an important predictor of heroin addiction. Wills, DuHamel, and Vaccaro (1995) found that self-control, as assessed by a scale they derived from a behavior rating scale by Kendall and Wilcox (1979), was an important predictor of substance abuse among adolescents and, in fact, seemed to mediate between temperament and substance abuse.…”
Section: Impulse Controlmentioning
confidence: 99%
“…It is one of the most powerful and adaptive human traits. A high level of self-control predicts better academic performance, efficient impulse control, fewer eating disorder symptoms, and lack of alcohol or other substance addiction problems (Storey, 1999). Self-controlling people are likely to save their money (Romal & Kaplan, 1995) and make desirable partners in relationships (Tangney, Baumeister, & Boone, 2004).…”
Section: Discussionmentioning
confidence: 99%